Intra- and Extra-Familial Victimization Experiences: Differentiating Between Incarcerated Serious Youth Offenders and Youth Rapists. Issue 15 (August 2019) - Yoder, Jamie R.; Hodge, Ashleigh I.; Ruch, Donna
Although research is becoming increasingly nuanced by exploring differential risk factors linked with types of youth offenders, typological distinctions have rarely been made between youth rapists and other serious youth offenders. This study tests the relative effects of intra- and extra-familial victimization—while holding other theoretically driven variables constant—on membership in three mutually exclusive youth offending groups: non-serious non-sexual offenders ( n = 4, 013), serious non-sexual offenders ( n = 2, 571), and rapists ( n = 489). Data were drawn from the Survey of Youth in Residential Placement (SYRP). Incarcerated youth ( N = 7, 073) were surveyed on multiple constructs. Using appropriate weights in analyses, a multinomial logistic regression (referencing serious offenders) revealed youth who were victims of intra-familial physical abuse (22%) and intra-familial forced sex (42%) had a decreased risk of being in the non-serious offender category relative to the serious offender category. Furthermore, intra-familial emotional abuse (75%) and intra-familial forced sex (202%) demonstrated an increased risk of being in the rapist category relative to serious offender category. Although extra-familial victimization was statistically significant, victimization within the family had larger effects when predicting rape group membership. The research and practice implications are discussed.